Organization of Guidance Services at Different Levels of Education: The Importance of Guidance Services in Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Guidance is an integral part of education these days. Guidance is provided at all levels of education—schools, colleges and universities. The aim of guidance is to help students adjust to their educational environment. Many students face problems in adjusting to their school or college life and are unable to cope up with these problems. Guidance services typically entail helping such students to face and overcome their problems so that they can attain holistic development in their educational environment. So, in the current trend, guidance and counseling are very much required for schoolcollege going students to identify their strength, weakness and at the same time work on their strength and area of interest to do wonders in future.